PENGARUH PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF PADA MATA PELAJARAN MATEMATIKA KELAS V MADRASAH IBTIDAIYAH NEGERI - Zaidatul Wahdiyah; Rora Rizky Wandini; Lailatun Nur Kamalia Siregar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The research that has been carried out is entitled "INFLUENCE PROJECT BASED LEARNING REGARDING THE ABILITY TO THINK CREATIVELY IN MATHEMATICS SUBJECT CLASS V MIN 5 LABUHANBATU" and has been based on problems that have been found in the field that indicators of mathematical ability have not been met, one of which is the ability to think creatively, where mathematics is still considered difficult and boring, and is carried out using conventional learning In fact, mathematics learning must have an appropriate learning model in order to attract students' attention. Where by involving students in learning, with the current curriculum project based learning be one of the options in implementing learning, project based learning always involves students in learning and can improve students' creative thinking abilities. The research methodology uses a pre-experimental design research type using one group pretest-posttest. In this research, the research population is 25 students and the research sample is the entire population, namely 25 students. The purpose of this research is to determine the results of students' creative thinking abilities after using project based learning in mathematics learning.Based on research conducted in class V MIN 5 LABUHANBATU, learning uses a model project based learning turned out to provide significant results on students' creative thinking in mathematics subjects. This can be seen through the average score of students' creative thinking abilities by implementing Project Based Learning, which is 85.00. Meanwhile, according to the results of the t test, a value of 0.000 was obtained so that sig(2tailed) < 0.05 which states that Ha accepted and HO rejected, the average student thinks creatively before implementing it Project Based Learning is 61.60